A composite lithium iron manganese phosphate positive electrode material and its preparation method and application
By forming a MOF cladding layer on the lithium manganese iron phosphate positive electrode material, the problems of poor electronic conductivity and cycling performance are solved, and the performance of efficient electrode materials is improved, which is suitable for industrial applications of lithium-ion batteries.
Patent Information
- Application Number
- CN202211611373.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-14
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-12-14
AI Technical Summary
The existing lithium manganese iron phosphate (LMFP) cathode materials have low electronic conductivity and ion diffusion rates and poor cycling performance, which limits their large-scale application in lithium-ion batteries.
Ultrasonic method is used to prepare MOF solution and mix it with lithium manganese iron phosphate powder and calcinate it to form a MOF cladding layer, which improves electron conductivity and enhances structural stability, and forms a composite lithium manganese iron phosphate positive electrode material.
It significantly improves the electronic conductivity and cycling performance of the electrode material, achieves high-rate performance, high-temperature storage and high-temperature cycling performance, and is suitable for large-scale industrial production.
Smart Images

Figure CN115947325B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and relates to a composite lithium manganese iron phosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] The booming development of new energy vehicles has led to a rapid increase in the demand for lithium-ion power batteries. At present, the main cathode materials for lithium-ion power batteries are lithium iron phosphate (LFP) and ternary materials. Among them, LFP has gradually become the preferred choice of energy storage and power battery companies due to its advantages such as high cost performance, high safety and small resource bottleneck. However, it has the problem of low energy density, which has become a key factor restricting the large-scale application of lithium iron phosphate.
[0003] Lithium manganese iron phosphate (LMFP) is a cathode material obtained by adding manganese to LFP. Manganese doping can make LMFP have a higher voltage platform (4.1V vs 3.4V), and the energy density of the battery is increased by about 15%. It is a cathode material with great application prospects. At present, LMFP cathode materials are still in the early stages of industrialization. The main reason is that LMFP has low electronic conductivity and ion diffusion rate, and poor cycle performance, which seriously affects its commercial implementation. Therefore, improving the electronic conductivity, ion transmission rate and cycle stability of LMFP materials is the current technical key.
[0004] CN111900344A discloses a method for preparing a carbon-coated lithium manganese iron phosphate positive electrode material. The invention first adopts a coprecipitation method to prepare NH4Mn x Fe 1-x PO4 precursor, then coated with carbon source, and calcined under inert atmosphere to obtain carbon-coated lithium manganese iron phosphate positive electrode material. This method can improve the phase purity, consistency and controllability of the positive electrode material, but this process ratio is difficult to accurately control and easily causes particle agglomeration problems.
[0005] CN106058220A discloses a method for preparing a titanium nitride and carbon double-coated lithium iron manganese phosphate composite material, which achieves the preparation of a lithium iron manganese phosphate composite material with uniform titanium nitride and carbon coating on the surface by adding a carbon source to a precursor and depositing a titanium nitride coating layer on the surface of LMFP by chemical vapor deposition. The coating layer has good uniformity and consistency, and has good charge and discharge rate performance as a lithium ion positive electrode material, but the process has low production efficiency and high cost, and does not mention the cycle performance of the lithium iron manganese phosphate composite material, and lacks reference value for practical application.
[0006] CN111129463A discloses a method for preparing a MOF-coated single crystal ternary cathode material and its precursor, wherein the core of the method adopts a high-nickel, low-manganese precursor synthesized by a coprecipitation method, and the outer shell adopts Mn and organic carboxylate to synthesize Mn-MOF, and the Mn of the outer shell is uniform at the atomic level. The ternary cathode material synthesized by this method overcomes the problems of poor circulation and thermal stability caused by high nickel, but the production conditions of the ternary material are harsh and the cost is high, and the high-nickel ternary material has poor circulation performance and safety performance, which hinders its large-scale application in the field of power batteries. Summary of the invention
[0007] The purpose of the present invention is to provide a composite lithium manganese iron phosphate positive electrode material and a preparation method and application thereof. The present invention effectively improves the electron and ion transmission capacity of LMFP and solves the problem of poor cycle stability of LMFP in the prior art.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a composite lithium iron manganese phosphate positive electrode material, the preparation method comprising the following steps:
[0010] (1) mixing a metal salt solution and an organic ligand solution, and obtaining a MOF solution by ultrasonic treatment;
[0011] (2) mixing the lithium manganese iron phosphate powder with the MOF solution obtained in step (1), and grinding to obtain a mixed material;
[0012] (3) calcining the mixture obtained in step (2) to obtain the composite manganese iron phosphate lithium positive electrode material.
[0013] In the preparation process of the composite lithium manganese iron phosphate positive electrode material according to the method of the present invention, on the one hand, the highly extended d-π conjugated system formed by the coordination bond of MOF and the π-π stacking effect between the organic ligands can significantly improve the electronic conductivity. After the MOF is carbonized under an inert atmosphere, the organic components in the MOF form a carbon matrix, which is evenly coated on the surface of LMFP, plays a bridging role, forms an electron transfer channel, and improves the conductivity of the LMFP electrode material; on the other hand, MOF is covered on the surface of the positive electrode material as a protective coating, reduces the side reaction between the active substance and the electrolyte, enhances the structural stability of the material, and thus improves the cycle performance of the electrode material. The battery made of LMFP as the positive electrode material of the lithium ion battery shows good high rate performance, high temperature storage and high temperature cycle performance.
[0014] Preferably, the solute of the metal salt solution in step (1) comprises magnesium salt and / or aluminum salt.
[0015] Preferably, the molar concentration of the metal salt solution is 0.2-10 mol / L, for example, 0.2 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, 5 mol / L or 10 mol / L, etc., preferably 0.5-2.0 mol / L.
[0016] Preferably, the solute of the organic ligand solution includes 2-methylimidazole and / or phthalic acid.
[0017] Preferably, the solvent of the organic ligand solution includes any one of methanol, ethanol or acetone, or a combination of at least two of them.
[0018] Preferably, the molar concentration of the organic ligand solution is 0.2-5 mol / L, for example, 0.2 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L or 5 mol / L, etc., preferably 0.5-2.0 mol / L.
[0019] Preferably, the temperature of the ultrasonic treatment in step (1) is 20-100°C, for example, 20°C, 40°C, 60°C, 80°C or 100°C, etc., preferably 60-80°C.
[0020] Preferably, the ultrasonic treatment time is 0.5 to 10 h, for example, 0.5 h, 1 h, 2 h, 5 h, 8 h or 10 h.
[0021] The present invention prepares the MOF solution by an ultrasonic method, which can make the material nucleation uniform, reduce the crystallization time, and form a smaller degree of crystallinity.
[0022] Preferably, the chemical formula of the lithium manganese iron phosphate powder in step (2) is LiMn x Fe 1-x PO4, where 0.1≤x<1.
[0023] Preferably, the grinding treatment in step (2) comprises ball milling.
[0024] Preferably, stirring is performed while the grinding process is performed.
[0025] Preferably, the stirring speed is 300-800 rpm, for example, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm or 800 rpm.
[0026] Preferably, the grinding treatment time is 0.5 to 5 h, for example: 0.5 h, 1 h, 2 h, 3 h, 4 h or 5 h.
[0027] Preferably, the atmosphere of the calcination treatment in step (3) includes a nitrogen atmosphere.
[0028] Preferably, the calcination temperature is 200-600°C, for example, 200°C, 300°C, 400°C, 500°C or 600°C.
[0029] Preferably, the calcination treatment time is 2 to 12 hours, for example: 2 hours, 3 hours, 5 hours, 6 hours, 8 hours or 12 hours.
[0030] In a second aspect, the present invention provides a composite lithium iron manganese phosphate positive electrode material, which is prepared by the method described in the first aspect, and the composite lithium iron manganese phosphate positive electrode material includes a lithium iron manganese phosphate core and a MOF coating layer arranged on the surface of the lithium iron manganese phosphate core.
[0031] The coating layer of the composite manganese iron phosphate lithium positive electrode material of the present invention has good uniformity, consistency and conductivity. The preparation process of the method is simple and controllable, and is easy to be mass-produced industrially.
[0032] Preferably, based on the mass of the composite lithium manganese iron phosphate positive electrode material being 100%, the mass fraction of the MOF coating layer is 0.05-0.2%.
[0033] In a third aspect, the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the composite lithium iron manganese phosphate positive electrode material as described in the second aspect.
[0034] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet as described in the third aspect.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) The coating layer of the composite manganese iron phosphate lithium positive electrode material of the present invention has good uniformity, consistency and conductivity. The preparation process of the method is simple and controllable, and is easy to be mass-produced industrially.
[0037] (2) The battery made of the composite manganese iron phosphate lithium positive electrode material of the present invention has a discharge capacity of more than 142 mAh / g, a 3C rate discharge of more than 97.8%, and a capacity retention rate of more than 88.5% after 1500 cycles at 45°C and 1C. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a comparison chart of the cycle performance of the composite lithium manganese iron phosphate positive electrode material described in Examples 1-3 and Comparative Example 1. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0040] The lithium iron manganese phosphate powder of the present invention is prepared by the following method:
[0041] Lithium hydroxide, manganese nitrate, iron nitrate and phosphoric acid were weighed according to the molar ratio of Li:Mn:Fe:P=1.05:0.5:0.5:1, added into deionized water, dispersed and stirred in a ball mill, and stirred at a stirring speed of 800 rpm for 5 h to obtain LiMn 0.5 Fe 0.5 PO4 precursor was placed in a box furnace protected by nitrogen atmosphere, heated to 800℃ at a heating rate of 5℃ / min, kept warm for 10h, and then cooled to room temperature to obtain lithium manganese iron phosphate positive electrode material, expressed as LiMn 0.5 Fe 0.5 PO4.
[0042] Example 1
[0043] This embodiment provides a composite lithium iron manganese phosphate positive electrode material, and the preparation method of the composite lithium iron manganese phosphate positive electrode material is as follows:
[0044] (1) Dissolve magnesium chloride in ethanol to prepare a solution A with a metal ion concentration of 1.0 mol / L, and dissolve terephthalic acid in ethanol to prepare a solution B with an organic ligand concentration of 1.0 mol / L. Add solution A to solution B, and ultrasonicate at 50°C for 2 h to obtain a MOF solution;
[0045] (2) adding LMFP powder into solution C at a solid content of 40%, ball milling and stirring at a speed of 500 rpm for 2 h, and then drying to obtain a mixed material;
[0046] (3) The mixed material obtained in step (2) is calcined at 500° C. for 5 h, and after cooling, the composite manganese iron phosphate lithium positive electrode material is obtained, wherein the mass fraction of the MOF coating layer in the composite manganese iron phosphate lithium positive electrode material is 0.1%.
[0047] Example 2
[0048] This embodiment provides a composite lithium iron manganese phosphate positive electrode material, and the preparation method of the composite lithium iron manganese phosphate positive electrode material is as follows:
[0049] (1) Aluminum chloride was dissolved in ethanol to prepare a solution A with a metal ion concentration of 0.8 mol / L, and 2-methylimidazole was dissolved in ethanol to prepare a solution B with an organic ligand concentration of 1.2 mol / L. Solution A was added to solution B, and ultrasonicated at 60°C for 2 h to obtain a MOF solution;
[0050] (2) adding LMFP powder into solution C at a solid content of 40%, ball milling and stirring at a speed of 500 rpm for 2 h, and then drying to obtain a mixed material;
[0051] (3) The mixed material obtained in step (2) is calcined at 550° C. for 5 h, and after cooling, the composite manganese iron phosphate lithium positive electrode material is obtained, wherein the mass fraction of the MOF coating layer in the composite manganese iron phosphate lithium positive electrode material is 0.15%.
[0052] Example 3
[0053] This embodiment provides a composite lithium iron manganese phosphate positive electrode material, and the preparation method of the composite lithium iron manganese phosphate positive electrode material is as follows:
[0054] (1) Dissolve magnesium chloride in ethanol to prepare a solution A with a metal ion concentration of 0.5 mol / L, and dissolve terephthalic acid in ethanol to prepare a solution B with an organic ligand concentration of 1.5 mol / L. Add solution A to solution B, and ultrasonicate at 50°C for 2 h to obtain a MOF solution;
[0055] (2) adding LMFP powder into solution C at a solid content of 40%, ball milling and stirring at a speed of 500 rpm for 2 h, and then drying to obtain a mixed material;
[0056] (3) The mixed material obtained in step (2) is calcined at 500° C. for 5 h, and after cooling, the composite manganese iron phosphate lithium positive electrode material is obtained, wherein the mass fraction of the MOF coating layer in the composite manganese iron phosphate lithium positive electrode material is 0.2%.
[0057] Comparative Example 1
[0058] The only difference between this comparative example and Example 1 is that no MOF coating layer is provided, and other conditions and parameters are exactly the same as those in Example 1.
[0059] Performance Test:
[0060] The positive electrode is a composite lithium iron manganese phosphate positive electrode material prepared in Example 1-3, and the negative electrode material is a graphite carbon material, which is matched with a PE / PP polymer material as a separator, and is assembled into a roll core by winding or laminating, encapsulated in an aluminum shell or aluminum-plastic film, and injected with a lithium ion electrolyte composed of an organic solvent such as EC / EMC and LiPF6, assembled into an aluminum shell or soft-pack lithium ion battery, and the performance of the lithium ion battery is tested. The test results are shown in Table 1:
[0061] Table 1
[0062]
[0063]
[0064] As can be seen from Table 1, from Examples 1-3, the discharge capacity of the battery made of the composite manganese iron lithium phosphate positive electrode material of the present invention can reach more than 142 mAh / g, the 3C rate discharge can reach more than 97.8%, and the capacity retention rate can reach more than 88.5% after 1500 cycles at 45°C 1C.
[0065] The cycle performance comparison of the composite lithium manganese iron phosphate positive electrode material described in Examples 1-3 and Comparative Example 1 is shown in the figure below. Figure 1 As shown, by comparing Examples 1-3 with Comparative Example 1, it can be seen that in the preparation process of the composite lithium manganese iron phosphate positive electrode material of the method of the present invention, on the one hand, the highly extended d-π conjugated system formed by the coordination bond of MOF and the π-π stacking effect between the organic ligands can significantly improve the electronic conductivity. After the MOF is carbonized under an inert atmosphere, the organic components in the MOF form a carbon matrix, which is evenly coated on the surface of the LMFP, plays a bridging role, forms an electron transfer channel, and improves the conductivity of the LMFP electrode material; on the other hand, MOF is covered on the surface of the positive electrode material as a protective coating, reduces the side reaction between the active substance and the electrolyte, enhances the structural stability of the material, and thus improves the cycle performance of the electrode material. The battery made of LMFP as the positive electrode material of the lithium ion battery shows good high rate performance, high temperature storage and high temperature cycle performance.
[0066] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a composite lithium manganese iron phosphate positive electrode material, characterized in that: The preparation method comprises the following steps: (1) mixing a metal salt solution and an organic ligand solution, and subjecting the mixture to ultrasonic treatment to obtain a MOF solution; (2) mixing the lithium manganese iron phosphate powder with the MOF solution obtained in step (1), and grinding to obtain a mixed material; (3) calcining the mixed material obtained in step (2) to obtain the composite manganese iron phosphate lithium positive electrode material; The temperature of the ultrasonic treatment in step (1) is 60 to 80° C., and the time of the ultrasonic treatment is 0.5 to 10 h.
2. The preparation method according to claim 1, characterized in that The solute of the metal salt solution in step (1) includes magnesium salt and / or aluminum salt.
3. The preparation method according to claim 1, characterized in that: The molar concentration of the metal salt solution is 0.2-10 mol / L.
4. The preparation method according to claim 3, characterized in that: The molar concentration of the metal salt solution is 0.5-2.0 mol / L.
5. The preparation method according to claim 1, characterized in that: The solute of the organic ligand solution includes 2-methylimidazole and / or phthalic acid.
6. The preparation method according to claim 1, characterized in that: The solvent of the organic ligand solution includes any one of methanol, ethanol or acetone, or a combination of at least two of them.
7. The preparation method according to claim 1, characterized in that: The molar concentration of the organic ligand solution is 0.2-5 mol / L.
8. The preparation method according to claim 7, characterized in that: The molar concentration of the organic ligand solution is 0.5-2.0 mol / L.
9. The preparation method according to claim 1, characterized in that: The chemical formula of the lithium iron manganese phosphate powder in step (2) is LiMn x Fe 1-x PO4, where 0.1≤x<1.
10. The preparation method according to claim 1, characterized in that: The grinding treatment in step (2) includes ball milling.
11. The preparation method according to claim 1, characterized in that: The grinding process is performed while stirring.
12. The preparation method according to claim 11, characterized in that: The stirring speed is 300-800 rpm.
13. The preparation method according to claim 1, characterized in that: The grinding treatment time is 0.5 to 5 hours.
14. The preparation method according to claim 1, characterized in that: The atmosphere for the calcination treatment in step (3) includes a nitrogen atmosphere.
15. The preparation method according to claim 1, characterized in that: The calcination temperature is 200-600°C.
16. The preparation method according to claim 1, characterized in that: The calcination treatment time is 2 to 12 hours.
17. A composite lithium manganese iron phosphate positive electrode material, characterized in that: The composite lithium iron manganese phosphate positive electrode material is prepared by the method according to any one of claims 1 to 16, and the composite lithium iron manganese phosphate positive electrode material comprises a lithium iron manganese phosphate core and a MOF coating layer arranged on the surface of the lithium iron manganese phosphate core.
18. The composite lithium iron manganese phosphate positive electrode material according to claim 17, characterized in that: Taking the mass of the composite manganese iron phosphate lithium positive electrode material as 100%, the mass fraction of the MOF coating layer is 0.05-0.2%.
19. A positive electrode plate, characterized in that: The positive electrode plate comprises the composite lithium manganese iron phosphate positive electrode material as described in claim 17 or 18.
20. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as claimed in claim 19.
